Simulation and modeling for full self-driving platoons with human factors in smart city - Meng, Qunyao (Nanyang Technological University, 2024)
The paper investigates the ways of interaction that appear between Autonomous Vehicle Platoons (VP) and other road vehicles using a new decision-making framework based on game theory. The basis of the interaction model focuses on these vehicle connections, in terms of a non-cooperative game, mainly on the Nash equilibrium to decide about it. To describe better how these dynamics function when it comes to safety, an experiment was conducted by proposing a pruning approach referred to as the conditionally pruning method. Such an innovative technique is intended to maintain harmony between the separate purposes of each vehicle and the supreme aim of safe navigation at all times. To evaluate the efficacy of the model in portraying levels of aggressive driving, both a comprehensive assessment and empirical test data from different cases were used. These aids in identifying whether vehicles can merge into a platoon or do not allow others to merge with it by serving as an important factor in such an aspect, thus showing successful management of car behavior on the road.